ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP EFEKTIVITAS PENERAPAN ANGGARAN BERBASIS KINERJA (STUDI KASUS PADA SKPD PEMERINTAH KABUPATEN GROBOGAN) - Sabtari Nawastri; Abdul Rohman (Diponegoro Journal of Accounting, 2015)
Budgeting approach focuses on the efficiency of the performance of an activity. Budget is drawn very closely related to the public (community), so that the local government is required to manage its finances with the principle of measurement of performance (value for money). Realization of performance-based budgeting is expected to eliminate the negative view of the public about the performance of local government. The purpose of this study was to analyze the factors that influence the effectiveness of the implementation of the Performance-Based Budgeting Purwodadi County Government. The study population was all SKPD in Central Java Grobogan District Government. Sampling method used in this research is census sampling method. The sample used in this study were all SKPD in Central Java Grobogan District Government, amounting to 31 SKPD. The data used is primary data obtained from questionnaires. The analysis technique used is multiple linear regression analysis. Based on the research results, the competence of human resources, information, performance measurement, and leadership style has positive influence on the effectiveness of performance-based budgeting and commitment while goal orientation has no effect on the effectiveness of performance-based budgeting. Based on the goodness of the model, the regression model can be used to predict the effectiveness of performance-based budgeting. While the effectiveness of performance-based budgeting can be explained by the six variables: the competence of human resources, information, goal orientation, performance measurement, leadership style and commitment of 89.6%.